Support for midlife anxiety diagnosis as an independent risk factor for dementia: a systematic review. Issue 4 (30th April 2018) - Gimson, Amy; Schlosser, Marco; Huntley, Jonathan D; Marchant, Natalie L
Abstract : Objectives: Anxiety is an increasingly recognised predictor of cognitive deterioration in older adults and in those with mild cognitive impairment. Often believed to be a prodromal feature of neurodegenerative disease, anxiety may also be an independent risk factor for dementia, operationally defined here as preceding dementia diagnosis by ≥10 years. Design: A systematic review of the literature on anxiety diagnosis and long-term risk for dementia was performed following published guidelines. Setting and participants: Medline, PsycINFO and Embase were searched for peer-reviewed journals until 8 March 2017. Publications reporting HR/OR for all-cause dementia based on clinical criteria from prospective cohort or case–control studies were selected. Included studies measured clinically significant anxiety in isolation or after controlling for symptoms of depression, and reported a mean interval between anxiety assessment and dementia diagnosis of at least 10 years. Methodological quality assessments were performed using the Newcastle-Ottawa Scale. Outcome measure: HR/OR for all-cause dementia. Results: Searches yielded 3510 articles, of which 4 (0.02%) were eligible. The studies had a combined sample size of 29 819, and all studies found a positive association between clinically significant anxiety and future dementia. Due to the heterogeneity between studies, a meta-analysis was not conducted. Conclusions: Clinically significant anxiety in midlife was associated with an increased risk of dementia over an interval of at least 10 years. These findings indicate that anxiety may be a risk factor for late-life dementia, excluding anxiety that is related to prodromal cognitive decline. With increasing focus on identifying modifiable risk factors for dementia, more high-quality prospective studies are required to clarify whether clinical anxiety is a risk factor for dementia, separate from a prodromal symptom.